Leveraging IoT and CFD to optimize solar PV module performance in high-temperature environments; case study: Kirkuk, Iraq - Yaareb Elias Ahmed; Jagadeesh Pasupuleti; Firas Basim Ismail; Suad Hassan Danook; Fadhil Khadoum alhousni; Mohammad Reza Maghami (Unconventional Resources)
-Solar photovoltaic (PV) systems are increasingly employed as a sustainable energy source. However, their efficiency is significantly affected by high operating temperatures, especially in regions like Kirkuk, Iraq, with high solar irradiance and ambient temperatures. Cooling systems can mitigate this issue by maintaining optimal operating temperatures, thereby improving system performance and lifespan. This research investigates the impact of a controlled cooling system on solar PV module performance through a combination of experimental and computational fluid dynamics (CFD) simulations. An IoT-based control system, utilizing an Ewelink Android mobile app, was implemented to remotely monitor and control the cooling system. Two solar modules were utilized: one with a controlled cooling system and the other without cooling. The experimental setup involved monitoring the temperature and power output of both modules under various environmental conditions in Kirkuk, Iraq. CFD simulations were employed to visualize and analyze the temperature distribution and airflow patterns around the modules. The results from both experimental and simulation studies demonstrated that the controlled cooling system effectively reduced the module temperature, leading to a significant improvement in energy output. The IoT-based control system enabled precise regulation of the cooling system, further enhancing the efficiency and reliability of the PV system. The CFD simulations provided valuable insights into the thermal behavior of the modules, helping to identify areas of high temperature concentration and optimize the cooling system design. The findings of this research highlight the importance of controlled cooling systems in enhancing the performance and longevity of solar PV systems, particularly in regions with high solar irradiance and ambient temperatures like Kirkuk, Iraq. By implementing effective cooling strategies, it is possible to maximize the energy output of solar PV systems and contribute to a more sustainable energy future.